Homology modeling and docking study of chalcone synthase gene (CfCHS) from Coleus forskohlii. Issue 1 (31st December 2016) - Awasthi, Praveen; Jamwal, Vijay Lakshmi; Kapoor, Nitika; Rasool, Shafaq
Abstract: Flavonoids are important secondary metabolites in plants. Chalcone synthase (CHS) catalyzes the first committed step in the flavonoids biosynthesis. CHS belongs to type ΙΙΙ polyketide synthases that are known for their broad substrate specificity and catalytic potential toward a wide range of thioesters, to produce diverse novel polyketides of pharmaceutical importance. In this study, an in silico approach was used to understand the structure and function of CHS protein from an important medicinal plant Coleus forskohlii . A homology model of CfCHS was built and docking studies were carried out using 25 ligands. Best four docked ligands in proposed binding pocket of CfCHS were: Cinnamoyl CoA, 2-Carbamoylbenzoyl CoA, Benzoyl CoA and p-Coumaroyl CoA. Cys 164, His 304, and Asn 337 were found to be catalytic residues of CfCHS. Further two important residues, Phe 216 and Phe 266, were found to be the gatekeeper residues involved in π – π interaction with ligands. Present study revealed broad spectrum substrate profile of CfCHS and important key residues involved in substrate binding. This is the first report of homology modeling and docking analysis of CHS from C. forskohlii .